NUTRITIONAL AND EPIDEMIOLOGICAL CAUSES OF CHOLELITHIASIS: A CROSS SECTIONAL STUDY OF THE PARADIGM SHIFT IN THE RISK FACTORS AT KHYBER PAKHTUNKHWA - Dr. Fazia Ghaffar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Cholelithiasis has been regarded as one of the one of the most prevalent disease in the gastrointestinal disorders with a larger disease and emergency surgical burden. Many factors contribute to the development of gall stones; genetic and predominantly dietary and life style factors. No such studies have previously been done to determine the contributing risk factors of cholelithiasis in Khyber Pakhtunkhwa.OBJECTIVES: (1).  To determine the socio demographic risk factors of cholelithiasis at district          Peshawar, Pakistan. (2). To analyze the dietary intake patterns, macronutrient densities of the diets, and physical activity patterns of the patients METHODS: A total of 125 patients (being calculated at 95% confidence interval and 1% odds ratio) were recruited after written consents. Gall stones and their sizes were confirmed by ultrasonography. Socio demographic characteristics, anthropometric measurements, biochemical tests for liver function, clinical symptoms of malnutrition and disease associated were examined, Food frequency (daily, weekly, monthly) for different food groups were considered. Based on 72 hours recall mean macronutrient intakes, their percent contribution to daily energy intakes, and physical activity patterns were analyzed through WHO standardized IPAQ tool. Data was analyzed through SPSS for both continuous and categorical variables.RESULTS: Among the study sample 95.4% patients were females, 97% married, 64% females, illiterate and 92% being housewives. Data of the male patients and husbands of the female patients collectively 53% were illiterate with low paid jobs while some were engaged in some government jobs. About 56% of the sample were living in extended family system, having children in the 5-9 category with the most common family size of 10-14 members (56%). About 55.2 % patients reported family history of gall stones. Majority of the patients had multiple stones of different sizes common being 2.2 cm. Clinical symptoms of iron and B complex vitamin deficiencies were commonly observed. Majority of the patients were referred to Ultrasonographic scans due to frequent GIT disturbances associated with gall stones. Mean age of the sample was 43.2± 21.93, while BMI (25.73 ±1.85), percent body fat (36.25±7.97) and % Visceral fat (9.45±19.76) showed a strong obesity and overweight trend (39.2% and 58.4% respectively) mainly the truncal obesity. The dietary frequency showed an overall poor food choice with higher intakes of wheat-based staples, rice, lentils, beef, chapli kabab (the local beef Pattie with herbs, spices and deep fried in tallow) and intake of seasonal cooked vegetables was common. Alarmingly most of the sample consumed white sugar and hydrogenated fat (ghee) were common. The overall consumption of energy and energy nutrients were higher while dietary protein and fiber were quite low. Physical activity patterns showed 43.8% inactive, 46.2% minimally active and 49.6% patients had >5 sitting hours. The data showed strong associations with many of the study parameters.CONCLUSION: The current study indicated age, being female gender, multiparity, larger family sizes, obesity, poor dietary choices, inactivity as the major contributing factors of cholelithiasis in this region.